Profile of patients undergoing outpatient surgery in otorhinolaryngology (Research, Society and Development, 2023)
Outpatient surgery has become increasingly widespread in Brazil and the world, in different areas of medicine. However, in the Brazilian otorhinolaryngology sector, this practice is still not widely used. The objective of the study was to trace the epidemiological profile of patients undergoing outpatient surgery in otorhinolaryngology. This is an observational, cross-sectional, descriptive and analytical study, with secondary data, through access to the electronic medical record of the private otorhinolaryngology service in Salvador. All patients undergoing outpatient surgery with complete medical records were included in the study, and those with incomplete medical records were excluded. For identifying the patient, the following were observed: age, gender, previous surgery, medications in use, comorbidities and ASA risk classification. In the surgical evaluation, the following were analyzes: time in the Pos Anesthetic Recovery Center (PARC), surgery time and hospitalization time, in addition to immediate and late post-surgical complications, post-complication approach and need for transfer to large health centers. A total of 868patients were studied, with a median age of 30 (IQR 18-40), 62% male and 8.9% with comorbidities. The rate of post-surgical complications was 2.2%, with no significant relation between this rate and age, hospitalization time or type of surgery. Conclusion: It was concluded that outpatient otorhinolaryngological surgery is feasible in patients with or without comorbidities, as long as they are classified as ASA 1 or ASA 2, as they cause lower rates of postoperative complications.